Developing an E-Module-Based Classroom Action Research Training Model - Sadimin, Sadimin; Hardyanto, Wahyu; Slamet, Achmad (The Journal of Educational Development, 2017)
The problem in this research is that the teachers have not carried out any independent action research to improve the learning quality and promotion. The purpose of this research is to analyze the actual model of classroom action research training for senior high school (SMA) teachers that have been carried out for years, to analyze the hypothetical model of an E-Module-based classroom action research training for high school teachers, and to analyze the final model of the E-Module-based classroom action research (CAR) training for SMA teachers. The method used in this study was research and development. The data were collected using interviews, documentation, observation, questionnaire, and test. The research results indicate that the final model of the E-Module-based classroom action research training is highly effective. The results of the extended trial show that the E-Module-based classroom action research training is able to properly facilitate teachers to implement and write a CAR research report independently and easily. E-Module-based CAR training assists teachers in understanding the CAR. This is understandable because E-Module-based CAR can be accessed anywhere and anytime through the Internet. The conclusion of this research is that E-Module-based CAR training makes it easy for teachers to conduct classroom action research because participants can access the E-Module via the browser.